Evaluation of the performance of granular fertilizer boom sprayer through computational fluid-particles-dynamid CFD simulation and scaled-down model analysis - Eng, Pei Ying (2018)
Malaysian Agricultural Research and Development Institute (MARDI) had bought two Japanese made granular fertilizer boom sprayers to test it on Malaysia’s Paddy field. In order to confirm the local feasibility of this fertilizer applicator, they had called UTHM researchers for proper experimental and numerical evaluations. A year of experimental assessments, the conclusion was supported with full range of numerical results and has a good agreement with MARDI’s findings. In this evaluation, ANSYS CFD was used for the fluid-particles-structure simulation while the statistical and image processing were made via MATLAB software. The simulation results were verified with the results from an in-house scaled-down model which was fabricated with the ratio of 2:15. The simulation was carried out by manipulating the angles of the boom sprayer collecting plates, ranging from 32o to 120o. The length of the collecting plate, the distance of the blow head, the sizes of the fertilizer and the air velocity of the blower were also varied in order to establish the correlations between the parameters. The ambient pressure was kept at 1 atm. Even though we managed to find 60o as the optimum collecting plate angle for most fertilizer sizes, there are two major factors that made it impossible to obtain good fertilizer distribution namely; the use of mixture of three different fertilizer (Nitrogen, Phosphorus and Potassium) sizes at once and the varying velocity profiles throughout the boom sprayer.